2021
DOI: 10.3390/su14010211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Consumer Preference for Green Tea with Eco-Friendly Certification in China

Abstract: The eco-friendly certification system is designed to ensure safe agricultural products to consumers while minimizing environmental pollution. However, despite its advantages, it is not widely adopted due to a possible decrease of farmers’ income. In order to provide implication for activating the eco-friendly certification system, this paper examines the attributes of green tea which affect consumers’ preferences and estimates consumers’ willingness to pay (WTP) for the eco-friendly certification in China. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In addition, it is essential to emphasize the difference between this study and previous investigations on consumer preferences for green tea products. For instance, in a study examining consumer preferences for green tea products with eco-friendly certification in China [15], significant influences of attributes such as place of production, size of production firm, certification, and type of green tea were observed. Specifically, green tea produced in different regions of China has been shown to have varying impacts on customer preferences, with South China, Jiangnan, and Southwest China influencing customer preferences by 16.2%, 23.2%, and 23.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it is essential to emphasize the difference between this study and previous investigations on consumer preferences for green tea products. For instance, in a study examining consumer preferences for green tea products with eco-friendly certification in China [15], significant influences of attributes such as place of production, size of production firm, certification, and type of green tea were observed. Specifically, green tea produced in different regions of China has been shown to have varying impacts on customer preferences, with South China, Jiangnan, and Southwest China influencing customer preferences by 16.2%, 23.2%, and 23.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is scarce research focusing on market research and consumer behavior, particularly regarding consumer preferences for specific attributes of green tea products. In China, Nam et al [15] studied consumer preferences for green tea with environmentally friendly certification, with the results showing that certain tea product attributes, such as the location of production, size of the production firm, certification, and type of green tea, affect consumer preferences, and thus, consumers are willing to pay more for green tea products with organic certification than for those without organic certification or without any certification at all. Another study by Yang et al [16] shows that the origin, organic labels, and brand attributes of Oolong tea are significant factors influencing consumers' purchasing decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…By studying the influencing factors and willingness to pay of consumers' purchase of ecological agricultural products, this paper believes that the core of consumers' purchase is health value and environmental value. With the frequent occurrence of food safety accidents in China, the basic requirement that consumers are willing to pay a premium for is the health and safety brought by its high quality [ 27 , 28 ]. Seubelt et al also found that price is a major factor in food choice from a sustainability perspective [ 29 ].…”
Section: Introductionmentioning
confidence: 99%